2018
DOI: 10.3389/fpsyg.2018.01421
|View full text |Cite
|
Sign up to set email alerts
|

From Their Point of View: Identifying Socio-Behavioral Profiles of Primary School Pupils Based on Peer Group Perception

Abstract: Our study adopted a person-based approach with the aim to identify socio-behavioral profiles of primary school students based on peer group perception. The study involved 109 classes and their teachers, from the first three grades of elementary school. The final student sample consisted of 424 children, aged 6–9 years (M = 94.9 months; SD = 9.7), of whom 58.3% were male. We used peer-group nomination to investigate the aspects that are linked to peer group acceptance and perception of classroom behaviors, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In line with this reasoning, highly accepted students tend to show lower levels of isolation (Prino et al, 2018), withdrawal (van den Berg et al, 2015), and loneliness (Newcomb, Bukowski, & Pattee, 1993). By contrast, rejected students reported, on average, more loneliness compared to other students (Buhs & Ladd, 2001).…”
Section: Lonelinessmentioning
confidence: 65%
See 1 more Smart Citation
“…In line with this reasoning, highly accepted students tend to show lower levels of isolation (Prino et al, 2018), withdrawal (van den Berg et al, 2015), and loneliness (Newcomb, Bukowski, & Pattee, 1993). By contrast, rejected students reported, on average, more loneliness compared to other students (Buhs & Ladd, 2001).…”
Section: Lonelinessmentioning
confidence: 65%
“…In line with these theories, a large body of research revealed that peer relationships are associated with students' academic and psychosocial development (Wentzel & Muenks, 2016). For instance, well-liked students are considered to be a relatively low-risk group for academic or psychosocial maladjustment compared to popular students (Cillessen & van den Berg, 2012;Ferguson & Ryan, 2019;North, Ryan, Cortina, & Brass, 2019;Pouwels et al, 2018;Prino, Pasta, Longobardi, Marengo, & Settanni, 2018;van den Berg et al, 2015).…”
Section: Peer Status and Differences In School Engagement And Lonelinessmentioning
confidence: 99%